Effect of Surface Modification on Viability of L929 Cells on Zirconia Nanocomposite Substrat - Aivazi, Moluk; Fathi, Mohammadhosein; Nejatidanesh, Farahnaz; Mortazavi, Vajihesadat; Hashemibeni, Batoul; Matinlinna, Jukka Pekka (Journal of Lasers in Medical Sciences, 2018)
Introduction: Zirconia bioceramic can be considered for metallic replacement in dental implant applications. A proper method of surface modification may promote better osseointegration. Methods: In study evaluated viability of fibroblast cell following surface treatment. Therefore, viability L929 cells were characterized using MTT assay and scanning electron microscopy. Results: The viability assessment determined significant differences A-Y-TZP20 without surface treatment as compared to laser surface treatment (B), laser surface treatment + hydroxyapatite-yttrium stabilized tetragonal zirconia nanocomposite coat (C) and control. This study demonstrated that L929 cells approximately proliferated and spread on A-Y-TZP20 nanocomposite disk in laser surface treatment(B), Laser surface treatment + hydroxiapatite-yttrium stabilized tetragonal zirconia nanocomposite coat (C) groups similar to control group. Conclusion: Laser surface treatment showed positive effect on the viability of L929 cells.